IFFCO-MC Crop Science a new beginning for crop and farmers protection - Dhingra, Anil (Indian Farming, 2017)
Like IFFCO, its joint venture IFFCO-MC Crop Science is also committed to the well being of the farmers and aims to go a long way in serving the crop protection needs of the farming community.